Quantification of CYFRA 21-1 and a CYFRA 21-1–anti-CYFRA 21-1 autoantibody immune complex for detection of early stage lung cancer. Issue 68 (22nd July 2019) - Song, Keum-Soo; Nimse, Satish Balasaheb; Warkad, Shrikant Dashrath; Oh, Ae-Chin; Kim, Taisun; Hong, Young Jun
Abstract : Population-based screening of stage 0–I lung cancer is crucial for saving lives. The CIC/CYFRA 21-1 ratio allows the detection of stage I lung cancer with 76.0% sensitivity and 87.5% specificity. Abstract : Population-based screening of stage 0–I lung cancer is crucial to save lives. In this article, we describe the development of a method for the detection of a CYFRA 21-1-autoantibody complex and CYFRA 21-1 in plasma samples. The CIC/CYFRA 21-1 ratio allows the detection of stage I–IV lung cancer with 76.0% sensitivity and 87.5% specificity.